Thermal Performance of Tilting-Pad Journal Bearing - Stolarski, T.A. (Engineering Transactions, 1992)
The results of studying, both theoretically and experimentally, the temperature profiles of tilting-pad journal bearing suggest that the heat transfer mechanism within the bearing has a significant effect on the thermal performance of the bearing and hence its overall performance. The heat transfer mechanism includes the heat transfer from the faces of the pads and the heat transfer occurring within the inter-pad cavities between the oil leaving the trailing edge of the pad and the shaft, and the cool supply oil. It is postulated that, in order to predict the performance of the bearing, it is necessary to couple computer modelling with experimental testing.